Occupational contact dermatitis in a gender perspective: North East Italian data 1996-2016: OCD in a gender perspective in North Italy - Mauro, Marcella; Bovenzi, Massimo; Larese Filon, Francesca (La Medicina del Lavoro, 2021)
Background: Occupational contact dermatitis (OCD) ranks high among occupational diseases in Europe, but little is known as regards OCD and jobs in a gender perspective. Objectives: To evaluate sex prevalence of OCD according to occupational sectors and agents involved. 27381 patients (1996–2016) with suspected irritant/allergic contact dermatitis (ICD-ACD) were evaluated in North-Eastern Italy. Each patient underwent: a standardized questionnaire, a dermatologist/occupational physician evaluation and a patch test. Results: Females were younger at diagnosis (35.2 ± 11.6 years vs 37.7 ± 12.6 in males, p< 0.001) and had a lower ICD prevalence (OR 0.58, C.I. 95% 0.51 - 0.66, p < 0.001). Job categories most involved differed between sexes, with highest rank for healthcare professionals in females and machinery mechanics and filters for males. In females ACD percentage was higher in all job categories. Conclusions: OCD characteristics differ between sexes, according to intrinsic and extrinsic factors. Use of personal care products, housekeeping products and outdoor work activities may account for different sensitization profiles.